Ankylosing Spondylitis Is Associated With Risk of New-Onset Obstructive Sleep Apnea: A Nationwide Population-Based Cohort Study - Tsao, Chien-Han; Huang, Jing-Yang; Huang, Hsin-Hsin; Hung, Yao-Min; Wei, James Cheng-Chung; Hung, Yin-Tsan (Frontiers in Medicine, 2019)
Objectives: investigating the risk of obstructive sleep apnea(OSA) among ankylosing spondylitis (AS) patients. Methods: We conducted a nationwide cohort study between 2003 and 2013 using the Taiwan National Health Insurance Research Database. The AS cohort included 2,210 patients who were newly diagnosed between 2003and 2013. Randomly selected non-AS controls were matched at a 1:4 ratio. The endpoint was set as an OSA occurrence or the end of 2013. Cumulative incidences, hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated after adjusting for age, gender, comorbidities, and co-medication. Multivariate analyses were performed using the Cox proportional hazards model. Due to the violation of the proportionality assumption, landmark analysis was conducted to explore the risk of OSA during specific follow-up periods. Results: The adjusted HR (aHR) of OSA in the AS group was 2.826 (95% C.I.= 1.727-4.625) compared to the control group. On landmark analysis, aHR was 7.919 (95% C.I.=3.169-19.792) for the AS group 0-24 months from the index date and decreased to 1.816 (95% C.I.=0.944-3.494) at ≥ 24 months from the index date. The increased risks of OSA in the AS group compared to the control group were found for both males and females (aHRs were 4.533 and 2.672). On age-stratified analysis, a significant risk only for the 40-59 age group with aHR of 3.913 (95% C.I.=1.890-8.102) Conclusions: A higher risk of developing OSA was found among newly diagnosed AS cohort during the 12-year follow-up period, especially within 2 years after newly diagnosed AS and in the 40-59 age group. Key Words: Ankylosing spondylitis, Obstructive sleep apnea, Population-based cohort study